2004
DOI: 10.1007/s00520-004-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer supportive care, improving the quality of life for cancer patients. A program evaluation report

Abstract: This evaluation of a free cancer supportive care program initiated in a hospital outpatient setting provides initial evidence of patient satisfaction and improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 39 publications
0
15
1
2
Order By: Relevance
“…Bien que le nombre de programmes qui leur sont destinés augmente, la littérature sur le sujet se fait rare. Deux rapports d'évaluation ont été publiés à ce sujet; tous deux décrivent et évaluent les programmes de soutien en oncologie offerts à l'Université Stanford aux patients atteints de cancer (voir Risendal et al, 2014et Rosenbaum et al, 2004 pour les descriptions et les résultats complets).…”
Section: Modèles De Soins Des Survivantsunclassified
See 1 more Smart Citation
“…Bien que le nombre de programmes qui leur sont destinés augmente, la littérature sur le sujet se fait rare. Deux rapports d'évaluation ont été publiés à ce sujet; tous deux décrivent et évaluent les programmes de soutien en oncologie offerts à l'Université Stanford aux patients atteints de cancer (voir Risendal et al, 2014et Rosenbaum et al, 2004 pour les descriptions et les résultats complets).…”
Section: Modèles De Soins Des Survivantsunclassified
“…L'objectif du premier programme (Stanford Cancer Supportive Care Program) était de soutenir les patients atteints de cancer pendant et après le traitement en répondant aux besoins entourant la qualité de vie (Rosenbaum et al, 2004). En majorité, les participants, surtout des femmes, avaient plus de 51 ans et souffraient principalement de cancer du sein.…”
Section: Modèles De Soins Des Survivantsunclassified
“…A similar study was published in 2004, in which cancer patients were invited to participate in the Stanford Cancer Supportive Care Program (SCSCP). 63 The SCSCP consisted of 11 different activities including fatigue management, nutrition, massage and restorative yoga. Of the 380 participants who participated in restorative yoga and evaluated their experience, 96% felt it reduced their stress, 74% felt an increase in energy, and 65% reported more restful sleep.…”
Section: Yoga For the Treatment Of Insomniamentioning
confidence: 99%
“…Other studies have shown that depression predicts cancer incidence or progression, although not all studies agree. Rosenbaum et al 18 discussed this effect in more detail. A randomized study that compared qol according to the survival of patients in the adjuvant and metastatic settings noted that an increase in qol included improved mood, appetite, and well-being, and hence facilitated longer survival 19.…”
Section: Implementing Integrative Oncologymentioning
confidence: 99%
“…Interpretation of qol differs with each person and is influenced by factors such as culture, age, and life experience. The patient evaluations from the Stanford Cancer Supportive Care Program suggest that participants received several benefits from the programs, such as an increase in sense of well-being, reduced feelings of stress, an increase in energy, more restful sleep, and an increase in hopefulness and empowerment—all ingredients that improve qol 18.…”
Section: Implementing Integrative Oncologymentioning
confidence: 99%